Pectoralis Major and Abdominis Rectus Musculocutaneous Flap Reconstruction for Sternal Wound Closure in Ectopia Cordis - Catherine H. Bautista, BS; Joanna Chen, BA; Laurel Ormiston, MD; Zachary J. Moore, BS; Adil Husain, MD; Barbu Gociman, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Ectopia cordis is a rare congenital condition resulting in extrathoracic positioning of the heart. The severity of presentation may vary with partial or complete displacement through sternal or diaphragmatic defects. Operative management is typically required, but due to the rarity of the condition, no standard exists for optimal closure. Reconstruction techniques can include compound local flap placement including pectoralis major, rectus abdominis, or latissimus dorsi flaps as well as synthetic material placement, autologous bone, and cartilage grafts to correct sternal deformity. This case report outlines the successful utilization of bilateral composite pectoralis major and rectus abdominal musculocutaneous flaps for complex staged closure of a sternal wound after creation of a cavopulmonary anastomosis in a 5-year-old patient with concomitant single-ventricle congenital heart disease. This single-staged closure after cardiac repair was performed without intra- or postoperative complications, and the patient demonstrated satisfactory healing with stable cardiac coverage at follow-up visit. This technique may present as an effective approach in complex sternal wound closure in patients with ectopia cordis.